Petrogenesis of Volcanic Arc Granites from Bayah Complex, Banten, Indonesia - Jemi Saputra Ahnaf; Aton Patonah; Haryadi Permana (Journal of Geoscience, Engineering, Environment, and Technology, 2019)
This research aimed to reveal the petrogenesis of granitic rocks of Bayah Complex starting from magma differentiation to exposing event, this research also intended to determine the tectonic environment. The methods carried out in this research include field observation, petrographic analysis using polarized light microscopy, and geochemical analysis using X-Ray Fluorescence (XRF) and Inductively Coupled Mass Spectrometry (ICP-MS). Petrographic analysis shows that Bayah granitic rocks are composed of quartz, plagioclase, and K-feldspar while the rest are amphibole, biotite, sericite, chlorite, epidote, and opaque. Based on its major oxide concentrations, Bayah granitic rocks classified as granite and diorite-quartz which have high-K calc-alkaline magma. 4 samples of granitic rocks showed the A/N+K+C > 1 molar ratios belonging to the peraluminous S-type granite index while the remaining 1 sample showed a molar ratio of A/N+ K+C < 1 and A/N+K > 1 which classified as metaluminous I-type granite. Accordingly, Bayah granitic rocks are S-type granite which crystallized from sediment-derived magma, the sediments itself estimated sourced from continental especially Malay Peninsula, Indonesian Tin Island, and Schwaner Mountains. During differentiation, the magma undergone crustal contamination reflected by the increase in both SiO2 0.51 wt% and Al2O3 1.95 wt%, and decrease in Fe2O3 + MgO 0.61 wt% from the pure composition of sediment-derived magma. Furthermore, the occurrence of crustal contamination also recognized from high concentrations of Rb and Ba which indicate the interaction of magma with the materials of continental crust. Regard to the exposing event, Bayah granitic rocks approximated to be exposed due to regional tectonic activity which caused Orogenesa I in the Early Oligocene to the Late Oligocene. Moreover, based on the plot of trace elements especially Rb, Y, Nb, Ta, and Yb on Harker and tectonic discriminant diagrams, Bayah granitic rocks are formed on volcanic-arc active continental margins in accordance with regional tectonic setting.